Opposite Modulation of Cell Migration by Distinct Subregions of Urokinase Connecting Peptide. Issue 7 (20th March 2013) - Franco, Paola; Carotenuto, Alfonso; Marcozzi, Cristina; Votta, Giuseppina; Sarno, Ciro; Iaccarino, Ingram; Brancaccio, Diego; De Vincenzo, Anna; Novellino, Ettore; Grieco, Paolo; Stoppelli, Maria Patrizia
Abstract Functional analysis of isolated protein domains may uncover cryptic activities otherwise missed. The serine protease urokinase (uPA) has a clear‐cut motogen activity that is catalytically independent and resides in its amino‐terminal growth factor domain (GFD, residues 1‐49) and connecting peptide region (CP, residues 132–158). To functionally dissect the CP region, we analysed the biological activity of two synthetic peptides corresponding to the N‐terminal [uPA‐(135–143), residues 135–143] and C‐terminal [uPA‐(144–158), residues 144–158] CP subregions. Most of the chemotactic activity of connecting peptide‐derived peptide (CPp, [uPA‐(135–158)]) for embryonic kidney HEK293/uPAR‐25 cells is retained by uPA‐(144–158) at nanomolar concentrations. In contrast, uPA‐(135–143) inhibits basal, CPp ‐, vitronectin‐ and fibronectin‐induced cell migration. Radioreceptor binding assays on intact HEK293 cells revealed that uPA‐(135–143) and uPA‐(144–158) are both able to compete with [125I]‐CPp, albeit with different binding affinities. The consequences of phospho‐mimicking, S138E substitution, were studied using [138E]uPA‐(135–158) and [138E]uPA‐(135–143) peptides. Unlike CPp, [138E]uPA‐(135–158) and [138E]uPA‐(135–143) exhibit remarkable inhibitory properties. Finally, analysis of the conformational preferences of the peptides allowed to identify secondary structure elements exclusively characterising the stimulatory CPp and uPA‐(144–158) versus the inhibitory uPA‐(135–143), [138E]uPA‐(135–158) and [138E]uPA‐(135–143) peptides. In conclusion, these data shed light on the cryptic activities of uPA connecting peptide, revealing the occurrence of two adjacent regions, both competing for binding to cell surface but conveying opposite signalling on cell migration.